Biosensors: Flexible, Graphene‐Coated Biocomposite for Highly Sensitive, Real‐Time Molecular Detection (Adv. Funct. Mater. 47/2016). (December 2016) - Wang, Lili; Jackman, Joshua A.; Ng, Wei Beng; Cho, Nam‐Joon
Abstract : Wearable sensors hold significant potential for healthcare monitoring and environmental science applications, and research into developing wearable, flexible sensors for tracking physiological markers is extensive. Toward this goal, N.‐J. Cho and co‐workers developed a high‐performance flexible sensor that includes lightweight pollen capsules and graphene, as shown on page 8623. The sensor demonstrates detection of ultralow concentrations of protein biomarkers for cancer diagnosis.